2021
DOI: 10.1371/journal.pcbi.1008898
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based investigation of the cancer protein secretory pathway

Abstract: Deregulation of the protein secretory pathway (PSP) is linked to many hallmarks of cancer, such as promoting tissue invasion and modulating cell-cell signaling. The collection of secreted proteins processed by the PSP, known as the secretome, is often studied due to its potential as a reservoir of tumor biomarkers. However, there has been less focus on the protein components of the secretory machinery itself. We therefore investigated the expression changes in secretory pathway components across many different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The well-known cancer suppressor gene, p53, closely controls various cellular signals involved in the cell-cycle, apoptosis, and senescence ( 39 ). A study based on machine learning showed that KIF20A and KIF23 were regulated by p53 and correlated with malignant transformation and tumor stage ( 40 ). Further, KIF15 knockdown strongly enhanced the expression of p53 and p21 protein in breast cancer cells ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The well-known cancer suppressor gene, p53, closely controls various cellular signals involved in the cell-cycle, apoptosis, and senescence ( 39 ). A study based on machine learning showed that KIF20A and KIF23 were regulated by p53 and correlated with malignant transformation and tumor stage ( 40 ). Further, KIF15 knockdown strongly enhanced the expression of p53 and p21 protein in breast cancer cells ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Saghaleyni and colleagues developed a module with eight machine learning algorithms for analyzing secreted protein profiles using gene expression data from thousands of normal human tissue and tumor samples. KIF20A and KIF23 , members of the kinesin family, were consistently among the top genes linked to malignant transformation [ 96 ]. Multi-Omic Graph Convolutional NETworks (MOGONET) effectively categorize multi-omic data, by both omics-specific learning and cross-omics correlation learning.…”
Section: Computational Algorithms For Data Integrationmentioning
confidence: 99%
“…14 Several key secretory pathway components and kinase or kinase-like protein related to pathophysiological characteristics of tumors that may be potential therapeutic targets have been reported. 15,16 Future research on carcinogenesis will be outlined and anti-tumor therapy will be improved with the identification of novel targets connected to the secretory pathway. This work investigated the molecular alterations and features of secretory pathway expression, categorized HCC according to the expression of gene in secretory pathway and created a gene signature to assess the effectiveness of chemotherapy and immunotherapy and predict the prognosis of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer secretome, which refers to an entire protein collection secreted via distinct secretory pathways by cancer cells, could represent potential therapeutic targets for a variety of cancers and tumor biomarkers 14 . Several key secretory pathway components and kinase or kinase‐like protein related to pathophysiological characteristics of tumors that may be potential therapeutic targets have been reported 15,16 . Future research on carcinogenesis will be outlined and anti‐tumor therapy will be improved with the identification of novel targets connected to the secretory pathway.…”
Section: Introductionmentioning
confidence: 99%